PASSIVE CAVITATION DETECTION DURING PULSED HIFU EXPOSURES OF EX VIVO TISSUES AND IN VIVO MOUSE PANCREATIC TUMORS - Li, Tong (2014)
Pulsed high-intensity focused ultrasound (pHIFU) has been demonstrated to enhance vascular permeability, disrupt tumor barriers and enhance drug penetration into tumor tissue through acoustic cavitation. Monitoring of cavitation activity during pHIFU treatments and knowing the ultrasound pressure levels sufficient to reliably induce cavitation in a given tissue are therefore very important. Here, three metrics of cavitation activity induced by pHIFU and evaluated by confocal passive cavitation detection were introduced: cavitation probability, cavitation persistence and the level of the broadband acoustic emissions. These metrics were used to characterize cavitation activity in several ex vivo tissue types (bovine tongue and liver and porcine adipose tissue and kidney) and gel phantoms (polyacrylamide and agarose) at varying peak-rarefactional focal pressures (1–12 MPa) during the following pHIFU protocol: frequency 1.1 MHz, pulse duration 1 ms, pulse repetition frequency 1 Hz. To evaluate the relevance of the measurements in ex vivo tissue, cavitation metrics were also investigated and compared in the ex vivo and in vivo murine pancreatic tumors that develop spontaneously in transgenic KPC mice and closely recapitulate human disease in their morphology. The cavitation threshold, defined at 50 % cavitation probability, was found to vary broadly among the investigated tissues (within 2.5–10 MPa), depending mostly on the water-lipid ratio that characterizes the tissue composition. Cavitation persistence and the intensity of broadband emissions depended both on tissue structure and lipid concentration. Both the cavitation threshold and broadband noise emission level were similar between ex vivo and in vivo pancreatic tumor tissue. The largest difference between in vivo and ex vivo settings was found in the pattern of cavitation occurrence throughout pHIFU exposure: it was sporadic in vivo, but ex vivo it decreased rapidly and stopped over the first few pulses. Cavitation activity depended on the interplay between the destruction and circulation of cavitation nuclei, which are not only used up by HIFU treatment but also replenished or carried away by circulation in vivo. These findings are important for treatment planning and optimization in pHIFU-induced drug delivery, in particular for pancreatic tumors.